Anti-aging waterproof coiled material
By adopting a multi-layer structure, the design of aging-resistant waterproof coil material, combined with the use of light stabilizers and anti-aging agents, the problem of aging of existing waterproof coil materials under light, heat and ultraviolet rays has been solved, and higher waterproof performance has been achieved. Aging resistance.
Patent Information
- Application Number
- CN202411828878.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-12
- Publication Date
- 2025-02-21
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Existing waterproof coils are prone to aging under the action of light, heat and ultraviolet rays, and commonly used anti-aging agents have problems with poor hydrophilicity, which affects their waterproof performance.
Design of aging-resistant waterproof coil with a multi-layer structure, including self-adhesive polymer modified asphalt adhesive layer, polyester tire base layer, glass fiber tire base layer and mineral pellet layer. By introducing light stabilizers and anti-aging agents, the materials are improved. Anti-UV and anti-aging properties.
It significantly improves the aging resistance and waterproof performance of the waterproof coil, enhances the mechanical properties and thermal stability of the material, and extends the service life.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The invention relates to the field of waterproof materials, and in particular to an aging-resistant waterproof coiled material. Background Art
[0002] At present, the more commonly used building waterproof membranes on the market are modified asphalt waterproof membranes and polymer waterproof membranes. Styrene-butadiene-styrene thermoplastic elastomer (SBS) modified asphalt waterproof membranes are widely used in building waterproofing due to their excellent high and low temperature performance. The SBS molecule has a small polarity, resulting in poor adhesion between it and many polar materials; the SBS molecular structure contains unsaturated double bonds and is easily oxidized by oxidizing substances such as ozone, resulting in a decrease in aging resistance. During use, the SBS modified asphalt waterproof membrane will also age due to the effects of light, heat and ultraviolet rays.
[0003] At present, the main methods to improve the anti-aging performance of waterproof membranes are to add organic antioxidants and inorganic antioxidants. Research results show that in the process of improving the anti-aging performance of asphalt, organic antioxidants will gradually age and lose their anti-aging effects. Kaolin, an inorganic antioxidant, is a layered inorganic material that can block heat, oxygen and ultraviolet rays when dispersed in asphalt, thereby improving the anti-aging performance of asphalt. However, the presence of a large number of hydroxyl groups on the surface of kaolin makes it exhibit strong hydrophilic and oleophobic properties, and its dispersibility in asphalt is very poor, so it cannot fully exert its anti-aging performance in asphalt.
[0004] Patent application number 201710865444.5 discloses a self-adhesive waterproof membrane. The invention introduces the anti-ultraviolet aging agent bis(2,2,6,6-tetramethyl-4-piperidinyl) sebacate. The molecule can generate active free radicals under the action of ultraviolet light and convert into inert groups, which has a good anti-ultraviolet aging effect. However, there are still some shortcomings: the polar ester group in the molecule increases the hydrophilicity, which is not conducive to the hydrophobic properties of the waterproof membrane. Summary of the invention
[0005] In order to solve the above technical problems, the object of the present invention is to provide an aging-resistant waterproof coiled material.
[0006] The purpose of the present invention can be achieved by the following technical solutions:
[0007] A single-layer roofing aging-resistant waterproofing roll material is a multi-layer structure, including a self-adhesive polymer modified asphalt rubber layer, a polyester base layer, a glass fiber base layer and a mineral granular layer. An isolation film is provided between the surface of one side of the self-adhesive polymer modified asphalt rubber layer and the roof, and the polyester base layer is adhered to the other side of the self-adhesive polymer modified asphalt rubber layer; the self-adhesive polymer modified asphalt rubber layer is adhered to one side of the polyester base layer, and the glass fiber base layer is adhered to the other side; the polyester base layer is adhered to one side of the glass fiber base layer, and the mineral granular layer is adhered to the other side; adjacent layers are adhered to each other by means of elastomer modified asphalt rubber, thus obtaining an aging-resistant waterproofing roll material.
[0008] Furthermore, the mineral granular material layer is ceramic magma material, the glass fiber base layer is glass fiber non-woven fabric, the polyester base layer is multifunctional polyester spunbond non-woven fabric, and the isolation membrane is a PE isolation membrane.
[0009] The elastomer-modified asphalt rubber is synthesized by the following steps:
[0010] Heat cycloalkane petroleum asphalt and natural rock asphalt to 150-160℃, add cycloalkane oil, SBS, polypropylene and acrylic rubber in turn, stir evenly, continue to heat to 180-190℃, react at this temperature for 35-45min, start the colloid mill to accelerate the swelling process and make the modifier polypropylene more homogenized, stop the colloid mill after 2-2.5h, stir at a constant speed for 2h, add light stabilizer, antioxidant, carbon black, continue to react for 80-90min, and obtain the elastomer modified asphalt rubber.
[0011] The self-adhesive polymer modified asphalt rubber is synthesized by the following steps:
[0012] Heat cycloalkyl petroleum asphalt to 150-160°C, then add maleic acid, SBS, polypropylene and polyisobutylene, stir evenly, continue to heat to 170-180°C, react at this temperature for 35-45 minutes, start the colloid mill to accelerate the swelling process, and make the modifier polypropylene more completely homogenized, stop the colloid mill after 1.5-2h, add polyolefin acetate, light stabilizer and antioxidant, stir at a uniform speed for 2h, add carbon black, continue stirring and reacting for 80-90min, and prepare the high temperature resistant hot air assisted self-adhesive polymer modified asphalt rubber used in the present invention.
[0013] The light stabilizer is synthesized by the following steps: Step A1: 2,2,6,6-tetramethylpiperidinol is added to methanol, and then a 2 mol / L sodium bicarbonate solution is added, and di-tert-butyl dicarbonate is added under stirring, and the mixture is stirred at 60° C. for 4 h, cooled, filtered, washed with deionized water, and vacuum dried at 65° C. for 8 h to obtain an intermediate 1,2,2,6,6-tetramethylpiperidinol, methanol, 2 mol / L sodium bicarbonate solution, and di-tert-butyl dicarbonate in an amount ratio of 0.1-0.2 mol:150 mL:200 mL:0.05 mol; During the reaction, 2,2,6,6-tetramethylpiperidinol reacts with di-tert-butyl dicarbonate, and the amino group is protected by Boc to obtain intermediate 1, which has the following structure:
[0017] Step A2: Dissolve the intermediate 1 in methanol, add dimethyl sulfoxide, stir to dissolve, add perfluorosebacic acid with stirring, then heat under reflux at 70°C for 2h, cool, filter, extract with ether, and vacuum dry at 75°C for 6h to obtain intermediate 2. The amount ratio of intermediate 1, methanol, dimethyl sulfoxide and perfluorosebacic acid is 0.2mol:150mL:2-3mL:0.1mol; During the reaction, intermediate 1 reacts with perfluorosebacic acid, and both carboxyl groups undergo esterification to obtain intermediate 2, the structure of which is shown below:
[0018] Step A3: adding intermediate 2 to trifluoroacetic acid, stirring, reacting at room temperature for 1-2 hours, then adding it to deionized water, stirring, extracting with ethyl acetate, and rotary evaporating to obtain a light stabilizer, wherein the ratio of intermediate 2 to trifluoroacetic acid is 0.1 mol: 0.3-0.4 mol; During the reaction, the intermediate 2 is deprotected by Boc with trifluoroacetic acid to form a diamino structure. The obtained light stabilizer (2,2,6,6-tetramethyl-4-piperidinyl) perfluorosebacate contains polyfluoroalkyl groups in the molecule, which enhances the hydrophobicity and lipophilicity and improves the waterproofness of the material. (2,2,6,6-tetramethyl-4-piperidinyl) perfluorosebacate can convert the active free radicals generated by thermoplastic elastomers and tackifying resins under the action of ultraviolet rays into stable inert groups, and has good anti-ultraviolet aging effect. The structure of the light stabilizer is shown below:
[0019] The antioxidant is synthesized by the following steps: Step B1: Add 3-aminopropyltrichlorosilane to n-hexane under the protection of nitrogen, stir and dissolve to obtain a mixed solution, then drop the mixed solution into trifluoroethanol under the protection of nitrogen flow, stir and react at 50° C. for 3 hours to obtain an intermediate 3, wherein the amount ratio of 3-aminopropyltrichlorosilane, n-hexane and trifluoroethanol is 0.1 mol: 200 mL: 0.3-0.4 mol; During the reaction, 3-aminopropyltrichlorosilane and trifluoroethanol undergo alcoholysis to generate intermediate 3, which is trifluoroethoxysilane containing a terminal amino group. A trifluoromethyl group is introduced into the structure to enhance the stability of intermediate 3 and improve the solubility of organic matter. The structure of intermediate 3 is shown below:
[0020] Step B2: Dissolve γ-methacryloxypropyltrimethoxysilane in methanol, add sodium carbonate, add tert-butyl peroxide with stirring, react at room temperature for 2 hours, extract with ether to obtain intermediate 4, the amount ratio of γ-methacryloxypropyltrimethoxysilane, methanol, sodium carbonate and tert-butyl peroxide is 0.1 mol: 150 mL: 0.02 g-0.04 g: 0.2-0.3 mol; During the reaction, the alkenyl group in γ-methacryloxypropyltrimethoxysilane is oxidized to an epoxy group by tert-butyl peroxide under alkaline conditions, and the structure of the generated intermediate 4 is shown below:
[0021] Step B3: Dissolve intermediate 4 in methanol, add sodium hydroxide, add intermediate 3 under stirring, react at room temperature for 6 hours, extract with ether to obtain intermediate 5, the amount ratio of intermediate 4, sodium hydroxide and intermediate 3 is 0.1 mol: 0.02-0.03 g: 0.1 mol; During the reaction, the amino group of intermediate 3 and the epoxy group of intermediate 4 undergo ring-opening addition, and the structure of intermediate 5 containing an alkyl alcohol hydroxyl group is shown below:
[0022] Step B4: Dissolve tert-butyldimethylsilyl chloride in DMF, add intermediate 5 under stirring, and react for 1.5 hours to obtain a silane coupling agent. The amount ratio of tert-butyldimethylsilyl chloride, DMF, and intermediate 5 is 0.1 mol: 150 mL: 0.1 mol; During the reaction, tert-butyldimethylsilyl chloride reacts with intermediate 5 to undergo silylation reaction, protecting the alcoholic hydroxyl group in the structure of intermediate 5. The generated silyl ether has good thermal stability. The silane coupling agent molecules obtained by the silylation reaction contain methoxysilyl, trifluoroethoxysilyl, and silyl ether groups. The hydrolysis of methoxysilyl to generate silanol can modify kaolin to obtain an organically modified inorganic antioxidant. The trifluoroethoxysilyl group has strong hydrophobicity and lipophilicity, which makes the antioxidant better dispersed and compatible in the modified asphalt, can reduce the surface energy of the material, and enhance the waterproofness of the material. The silyl ether group has high thermal stability, thereby enhancing the thermal stability of the material. The structure of the silane coupling agent is shown below:
[0036] Step B5: Mix the silane coupling agent and the 95% by volume ethanol solution in a beaker and ultrasonically disperse for 30 minutes to obtain a silane coupling agent hydrolyzate; pour kaolin and deionized water into a three-necked flask to prepare a kaolin slurry, add the silane coupling agent hydrolyzate while stirring, control the temperature to 80°C and stir at a speed of 500r / min for 4 hours, and filter under reduced pressure after cooling. Wash the filter cake with anhydrous ethanol for multiple times to remove unreacted silane coupling agent, put the filter cake into a vacuum drying oven at 80°C and dry it for 2 hours. After cooling, grind it and pass it through a 300-mesh sieve to obtain an antioxidant, and the amount ratio of the silane coupling agent, the 95% by volume ethanol solution, kaolin and deionized water is 0.5g:50mL:20g:400mL;
[0037] During the reaction, the silanol groups generated by the hydrolysis of the methoxysilyl groups in the silane coupling agent undergo dehydration condensation with the hydroxyl groups on the surface of kaolin to form ether bonds, thereby obtaining an antioxidant; the trifluoroethoxysilyl groups and silyl ether groups in the silane coupling agent molecules are retained in the antioxidant molecules; the trifluoroethoxysilyl groups enhance the hydrophobicity and lipophilicity, thereby enabling the antioxidant to be better dispersed and compatible in the modified asphalt, thereby better exerting the anti-aging properties and enhancing the waterproof properties of the material; kaolin itself is an inorganic filler with a toughening effect, and can enhance the mechanical properties of the material; the silyl ether groups have excellent thermal stability, which is beneficial to improving the thermal stability of the material.
[0038] Beneficial effects of the present invention: In the present invention, natural asphalt has excellent high temperature performance and corrosion resistance and aging resistance. Softeners cycloalkane oil and maleic acid are used to promote the swelling of additives, modifier polypropylene is used to improve various physical properties of modified asphalt coils, toughener acrylate rubber is used to improve the low temperature flexibility and elongation of modified asphalt coils, tackifier polyisobutylene is used to improve the initial adhesion and bonding durability of self-adhesive asphalt coils, and interface agent polyolefin acetate is used to reduce the surface tension of self-adhesive asphalt coils and improve the interfacial adhesion. By laying the polyester base layer on the self-adhesive asphalt layer, its superior elongation performance is fully utilized. With the help of the self-adhesive asphalt layer, it can adapt to small deformations of the base layer without cracking, and at the same time has self-healing properties. The glass fiber base layer next to the polyester base layer as a reinforcement layer can not only improve the tensile strength of the coil but also improve the dimensional stability of the coil.
[0039] The synthesized light stabilizer and antioxidant mainly improve the aging resistance of the modified asphalt coil. The light stabilizer (2,2,6,6-tetramethyl-4-piperidinyl) perfluoro sebacate contains polyfluoroalkyl groups in the molecule, which enhances the hydrophobicity and improves the waterproofness of the material; (2,2,6,6-tetramethyl-4-piperidinyl) perfluoro sebacate can also convert the active free radicals generated by thermoplastic elastomer and tackifying resin under the action of ultraviolet rays into stable inert groups, and has a good anti-ultraviolet aging effect. The antioxidant is kaolin modified with a silane coupling agent. The antioxidant is obtained by firmly combining the hydroxyl groups on the surface of kaolin with a silane coupling agent, thereby reducing the hydrophilicity and oleophobicity of kaolin, making kaolin better dispersed and compatible in asphalt. At the same time, trifluoroethoxysilyl groups and silyl ether groups are introduced. The trifluoroethoxysilyl groups enhance the waterproof performance of the material, and the silyl ether groups are beneficial to improving the thermal stability of the antioxidant molecules, so that the antioxidant can better exert its anti-aging performance. Kaolin itself is an inorganic filler, has a toughening effect, and enhances the mechanical properties of the material. DETAILED DESCRIPTION
[0040] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0041] Example 1
[0042] A light stabilizer is prepared by the following steps:
[0043] 2,2,6,6-tetramethylpiperidinol was added to methanol, and then 2mol / L sodium bicarbonate solution was added, di-tert-butyl dicarbonate was added under stirring, and the mixture was stirred at 60°C for 4 hours, cooled, filtered, washed with deionized water, and vacuum dried at 65°C for 8 hours to obtain the intermediate 1,2,2,6,6-tetramethylpiperidinol, methanol, 2mol / L sodium bicarbonate solution and di-tert-butyl dicarbonate in a ratio of 0.1mol:150mL:200mL:0.05mol;
[0044] Dissolve intermediate 1 in methanol, add dimethyl sulfoxide, stir to dissolve, add perfluorosebacic acid with stirring, then heat under reflux at 70°C for 2h, cool, filter, extract with ether, and vacuum dry at 75°C for 6h to obtain intermediate 2. The usage ratio of intermediate 1, methanol, dimethyl sulfoxide and perfluorosebacic acid is 0.2mol:150mL:2mL:0.1mol.
[0045] Add intermediate 2 to trifluoroacetic acid, stir, react at room temperature for 1 hour, then add it to deionized water, stir, extract with ethyl acetate, and rotary evaporate to obtain a light stabilizer. The ratio of intermediate 2 to trifluoroacetic acid is 0.1 mol:0.3 mol.
[0046] Example 2
[0047] A light stabilizer is prepared by the following steps:
[0048] 2,2,6,6-tetramethylpiperidinol was added to methanol, and then 2mol / L sodium bicarbonate solution was added, di-tert-butyl dicarbonate was added under stirring, and the mixture was stirred at 60°C for 4 hours, cooled, filtered, washed with deionized water, and vacuum dried at 65°C for 8 hours to obtain the intermediate 1,2,2,6,6-tetramethylpiperidinol, methanol, 2mol / L sodium bicarbonate solution and di-tert-butyl dicarbonate in a ratio of 0.15mol:150mL:200mL:0.05mol;
[0049] Dissolve intermediate 1 in methanol, add dimethyl sulfoxide, stir to dissolve, add perfluorosebacic acid with stirring, then heat under reflux at 70°C for 2h, cool, filter, extract with ether, and vacuum dry at 75°C for 6h to obtain intermediate 2. The usage ratio of intermediate 1, methanol, dimethyl sulfoxide and perfluorosebacic acid is 0.2mol:150mL:2.5mL:0.1mol.
[0050] Add intermediate 2 to trifluoroacetic acid, stir, react at room temperature for 1.5 hours, then add it to deionized water, stir, extract with ethyl acetate, and rotary evaporate to obtain a light stabilizer. The ratio of intermediate 2 to trifluoroacetic acid is 0.1 mol:0.35 mol.
[0051] Example 3
[0052] A light stabilizer is prepared by the following steps:
[0053] 2,2,6,6-tetramethylpiperidinol was added to methanol, and then 2mol / L sodium bicarbonate solution was added, di-tert-butyl dicarbonate was added under stirring, and the mixture was stirred at 60°C for 4 hours, cooled, filtered, washed with deionized water, and vacuum dried at 65°C for 8 hours to obtain the intermediate 1,2,2,6,6-tetramethylpiperidinol, methanol, 2mol / L sodium bicarbonate solution and di-tert-butyl dicarbonate in a ratio of 0.2mol:150mL:200mL:0.05mol;
[0054] Dissolve intermediate 1 in methanol, add dimethyl sulfoxide, stir to dissolve, add perfluorosebacic acid with stirring, then heat under reflux at 70°C for 2h, cool, filter, extract with ether, and vacuum dry at 75°C for 6h to obtain intermediate 2. The usage ratio of intermediate 1, methanol, dimethyl sulfoxide and perfluorosebacic acid is 0.2mol:150mL:3mL:0.1mol.
[0055] Add intermediate 2 to trifluoroacetic acid, stir, react at room temperature for 2 hours, then add it to deionized water, stir, extract with ethyl acetate, and rotary evaporate to obtain a light stabilizer. The ratio of intermediate 2 to trifluoroacetic acid is 0.1 mol:0.4 mol.
[0056] Example 4
[0057] An antioxidant is prepared by the following steps:
[0058] 3-aminopropyltrichlorosilane was added to n-hexane under the protection of nitrogen, and the mixture was dissolved by stirring to obtain a mixed solution. Then, the mixed solution was dripped into trifluoroethanol under the protection of nitrogen flow, and the mixture was stirred at 50° C. for 3 hours to obtain an intermediate 3, wherein the amount ratio of 3-aminopropyltrichlorosilane, n-hexane and trifluoroethanol was 0.1 mol: 200 mL: 0.3 mol;
[0059] Dissolve γ-methacryloxypropyltrimethoxysilane in methanol, add sodium carbonate, add tert-butyl peroxide with stirring, react at room temperature for 2 hours, extract with ether to obtain intermediate 4, the amount ratio of γ-methacryloxypropyltrimethoxysilane, methanol, sodium carbonate and tert-butyl peroxide is 0.1 mol: 150 mL: 0.02 g: 0.2 mol;
[0060] Dissolve intermediate 4 in methanol, add sodium hydroxide, add intermediate 3 under stirring, react at room temperature for 6 hours, extract with ether to obtain intermediate 5, the usage ratio of intermediate 4, sodium hydroxide and intermediate 3 is 0.1 mol: 0.02 g: 0.1 mol;
[0061] Dissolve tert-butyldimethylsilyl chloride in DMF, add intermediate 5 under stirring, and react for 1.5 hours to obtain a silane coupling agent. The amount ratio of tert-butyldimethylsilyl chloride, DMF and intermediate 5 is 0.1 mol: 150 mL: 0.1 mol;
[0062] The silane coupling agent and an ethanol solution with a volume fraction of 95% are mixed in a beaker and ultrasonically dispersed for 30 minutes to obtain a silane coupling agent hydrolyzate; kaolin and deionized water are poured into a three-necked flask to prepare a kaolin slurry, and the silane coupling agent hydrolyzate is added while stirring, the temperature is controlled to be 80°C and the stirring speed is 500r / min for 4 hours, and the reduced pressure is filtered after cooling, and the filter cake is washed with anhydrous ethanol for multiple times to remove the unreacted silane coupling agent, and the filter cake is placed in a vacuum drying oven at 80°C and dried for 2 hours. After cooling, it is ground and passed through a 300-mesh sieve to obtain an antioxidant, and the dosage ratio of the silane coupling agent, the ethanol solution with a volume fraction of 95%, the kaolin and the deionized water is 0.5g:50mL:20g:400mL.
[0063] Example 5
[0064] An antioxidant is prepared by the following steps:
[0065] 3-aminopropyltrichlorosilane was added to n-hexane under the protection of nitrogen, and the mixture was dissolved by stirring to obtain a mixed solution. Then, the mixed solution was dripped into trifluoroethanol under the protection of nitrogen flow, and the mixture was stirred at 50° C. for 3 hours to obtain an intermediate 3, wherein the amount ratio of 3-aminopropyltrichlorosilane, n-hexane and trifluoroethanol was 0.1 mol: 200 mL: 0.35 mol;
[0066] Dissolve γ-methacryloxypropyltrimethoxysilane in methanol, add sodium carbonate, add tert-butyl peroxide with stirring, react at room temperature for 2 hours, extract with ether to obtain intermediate 4, the amount ratio of γ-methacryloxypropyltrimethoxysilane, methanol, sodium carbonate and tert-butyl peroxide is 0.1 mol: 150 mL: 0.03 g: 0.25 mol;
[0067] Dissolve intermediate 4 in methanol, add sodium hydroxide, add intermediate 3 under stirring, react at room temperature for 6 hours, extract with ether to obtain intermediate 5, the usage ratio of intermediate 4, sodium hydroxide and intermediate 3 is 0.1 mol: 0.025 g: 0.1 mol;
[0068] Dissolve tert-butyldimethylsilyl chloride in DMF, add intermediate 5 under stirring, and react for 1.5 hours to obtain a silane coupling agent. The amount ratio of tert-butyldimethylsilyl chloride, DMF, and intermediate 5 is 0.1 mol: 150 mL: 0.1 mol;
[0069] The silane coupling agent and an ethanol solution with a volume fraction of 95% are mixed in a beaker and ultrasonically dispersed for 30 minutes to obtain a silane coupling agent hydrolyzate; kaolin and deionized water are poured into a three-necked flask to prepare a kaolin slurry, and the silane coupling agent hydrolyzate is added while stirring, the temperature is controlled to be 80°C and the stirring speed is 500r / min for 4 hours, and the reduced pressure is filtered after cooling, and the filter cake is washed with anhydrous ethanol for multiple times to remove the unreacted silane coupling agent, and the filter cake is placed in a vacuum drying oven at 80°C and dried for 2 hours. After cooling, it is ground and passed through a 300-mesh sieve to obtain an antioxidant, and the dosage ratio of the silane coupling agent, the ethanol solution with a volume fraction of 95%, the kaolin and the deionized water is 0.5g:50mL:20g:400mL.
[0070] Example 6
[0071] An antioxidant is prepared by the following steps:
[0072] 3-aminopropyltrichlorosilane was added to n-hexane under the protection of nitrogen, and the mixture was dissolved by stirring to obtain a mixed solution. Then, the mixed solution was dripped into trifluoroethanol under the protection of nitrogen flow, and the mixture was stirred at 50° C. for 3 hours to obtain an intermediate 3. The amount ratio of 3-aminopropyltrichlorosilane, n-hexane and trifluoroethanol was 0.1 mol: 200 mL: 0.4 mol.
[0073] Dissolve γ-methacryloxypropyltrimethoxysilane in methanol, add sodium carbonate, add tert-butyl peroxide with stirring, react at room temperature for 2 hours, extract with ether to obtain intermediate 4, the amount ratio of γ-methacryloxypropyltrimethoxysilane, methanol, sodium carbonate and tert-butyl peroxide is 0.1 mol: 150 mL: 0.04 g: 0.3 mol;
[0074] Dissolve intermediate 4 in methanol, add sodium hydroxide, add intermediate 3 under stirring, react at room temperature for 6 hours, extract with ether to obtain intermediate 5, the usage ratio of intermediate 4, sodium hydroxide and intermediate 3 is 0.1 mol: 0.03 g: 0.1 mol;
[0075] Dissolve tert-butyldimethylsilyl chloride in DMF, add intermediate 5 under stirring, and react for 1.5 hours to obtain a silane coupling agent. The amount ratio of tert-butyldimethylsilyl chloride, DMF, and intermediate 5 is 0.1 mol: 150 mL: 0.1 mol;
[0076] The silane coupling agent and an ethanol solution with a volume fraction of 95% are mixed in a beaker and ultrasonically dispersed for 30 minutes to obtain a silane coupling agent hydrolyzate; kaolin and deionized water are poured into a three-necked flask to prepare a kaolin slurry, and the silane coupling agent hydrolyzate is added while stirring, the temperature is controlled to be 80°C and the stirring speed is 500r / min for 4 hours, and the reduced pressure is filtered after cooling, and the filter cake is washed with anhydrous ethanol for multiple times to remove the unreacted silane coupling agent, and the filter cake is placed in a vacuum drying oven at 80°C and dried for 2 hours. After cooling, it is ground and passed through a 300-mesh sieve to obtain an antioxidant, and the dosage ratio of the silane coupling agent, the ethanol solution with a volume fraction of 95%, the kaolin and the deionized water is 0.5g:50mL:20g:400mL.
[0077] Example 7
[0078] An aging-resistant waterproof roll material is a multi-layer structure, including a self-adhesive polymer modified asphalt rubber layer, a polyester base layer, a glass fiber base layer and a mineral granular layer. An isolation membrane is provided between the surface of one side of the self-adhesive polymer modified asphalt rubber layer and the roof, and the polyester base layer is adhered to the other side of the self-adhesive polymer modified asphalt rubber layer; the self-adhesive polymer modified asphalt rubber layer is adhered to one side of the polyester base layer, and the glass fiber base layer is adhered to the other side; the polyester base layer is adhered to one side of the glass fiber base layer, and the mineral granular layer is adhered to the other side; adjacent layers are adhered by elastomer modified asphalt rubber. The mineral granular layer is a ceramic magma material, the glass fiber base layer is a glass fiber non-woven fabric, the polyester base layer is a multifunctional polyester spunbond non-woven fabric, and the isolation membrane is a PE isolation membrane.
[0079] The elastomer modified asphalt rubber comprises the following raw materials in parts by weight: 20 parts of cycloalkyl petroleum asphalt, 10 parts of natural rock asphalt, 10 parts of cycloalkyl oil, 7 parts of SBS, 10 parts of polypropylene, 2 parts of acrylic rubber, 0.5 parts of light stabilizer, 0.5 parts of antioxidant and 10 parts of carbon black.
[0080] The self-adhesive polymer modified asphalt rubber comprises the following raw materials in parts by weight: 35 parts of cycloalkyl petroleum asphalt, 15 parts of maleic acid, 8 parts of SBS, 8 parts of polypropylene, 4 parts of polyisobutylene, 3 parts of polyolefin acetate, 0.5 parts of light stabilizer, 0.5 parts of antioxidant and 10 parts of carbon black.
[0081] The weight and size of each layer of the aging-resistant waterproof roll material are as follows: the total thickness of the roll material is 4 mm, the lap width is 100 mm, the length of the roll material is 1000 mm, the thickness of the self-adhesive polymer modified asphalt rubber is 1.6 mm, the thickness of the polyester base layer is 1.0 mm, and the weight is 200 g / m 2 The thickness of the glass fiber base layer is 0.4mm and the weight is 80g / m 2 The thickness between the polyester base layer and the glass fiber base layer is 1mm, and the thickness of the mineral aggregate is 1mm.
[0082] The anti-aging waterproof coiled material is made by the following steps:
[0083] The naphthenic petroleum asphalt and natural rock asphalt were heated to 150°C, and naphthenic oil, SBS, polypropylene and acrylic rubber were added in sequence, stirred evenly, and the temperature was continued to rise to 180°C, and the reaction was carried out at this temperature for 35 minutes. The colloid mill was turned on to accelerate the swelling process and make the modifier polypropylene more completely homogenized. After 2 hours, the colloid mill was stopped, and the mixture was stirred at a constant speed for 2 hours. The light stabilizer obtained in Example 2, the antioxidant obtained in Example 5, and carbon black were added, and the reaction was continued for 80 minutes to obtain an elastomer-modified asphalt rubber.
[0084] The cycloalkyl petroleum asphalt was heated to 150°C, and then maleic acid, SBS, polypropylene and polyisobutylene were added, stirred evenly, and the temperature was continued to rise to 170°C, and the reaction was carried out at this temperature for 35 minutes. The colloid mill was turned on to accelerate the swelling process and make the modifier polypropylene more completely homogenized. After 1.5 hours, the colloid mill was stopped, polyolefin acetate, the light stabilizer obtained in Example 2 and the antioxidant obtained in Example 5 were added, stirred at a uniform speed for 2 hours, and carbon black was added. The reaction was continued with stirring for 80 minutes to prepare the high temperature resistant hot air assisted self-adhesive polymer modified asphalt rubber used in the present invention;
[0085] Lay the isolation membrane on one side of the self-adhesive polymer modified asphalt rubber layer, adhere the polyester base layer to the other side of the self-adhesive polymer modified asphalt rubber layer, adhere the glass fiber base layer to the surface of the polyester base layer, and adhere the mineral granular material layer to the surface of the glass fiber base layer to obtain the aging-resistant waterproof membrane.
[0086] Example 8
[0087] An aging-resistant waterproof roll material is a multi-layer structure, including a self-adhesive polymer modified asphalt rubber layer, a polyester base layer, a glass fiber base layer and a mineral granular layer. An isolation membrane is provided between the surface of one side of the self-adhesive polymer modified asphalt rubber layer and the roof, and the polyester base layer is adhered to the other side of the self-adhesive polymer modified asphalt rubber layer; the self-adhesive polymer modified asphalt rubber layer is adhered to one side of the polyester base layer, and the glass fiber base layer is adhered to the other side; the polyester base layer is adhered to one side of the glass fiber base layer, and the mineral granular layer is adhered to the other side; adjacent layers are adhered by elastomer modified asphalt rubber. The mineral granular layer is a ceramic magma material, the glass fiber base layer is a glass fiber non-woven fabric, the polyester base layer is a multifunctional polyester spunbond non-woven fabric, and the isolation membrane is a PE isolation membrane.
[0088] The elastomer modified asphalt rubber comprises the following raw materials in parts by weight: 30 parts of cycloalkyl petroleum asphalt, 15 parts of natural rock asphalt, 15 parts of cycloalkyl oil, 9 parts of SBS, 12 parts of polypropylene, 3 parts of acrylic rubber, 0.8 parts of light stabilizer, 0.8 parts of antioxidant and 15 parts of carbon black.
[0089] The self-adhesive polymer modified asphalt rubber comprises the following raw materials in parts by weight: 40 parts of cycloalkyl petroleum asphalt, 18 parts of maleic acid, 10 parts of SBS, 10 parts of polypropylene, 5 parts of polyisobutylene, 3.5 parts of polyolefin acetate, 1 part of light stabilizer, 1 part of antioxidant and 17 parts of carbon black.
[0090] The weight and size of each layer of the aging-resistant waterproof roll material are as follows: the total thickness of the roll material is 5 mm, the lap width is 100 mm, the length of the roll material is 1000 mm, the thickness of the self-adhesive polymer modified asphalt rubber is 1.8 mm, the thickness of the polyester base layer is 1.0 mm, and the weight is 210 g / m 2 The thickness of the glass fiber base layer is 0.45mm and the weight is 90g / m 2 The thickness between the polyester tire base and the glass fiber tire base is 1.2mm, and the thickness of the mineral aggregate is 1.1mm.
[0091] The anti-aging waterproof coiled material is made by the following steps:
[0092] The naphthenic petroleum asphalt and natural rock asphalt were heated to 155°C, and naphthenic oil, SBS, polypropylene and acrylic rubber were added in sequence, stirred evenly, and the temperature was continued to rise to 185°C, and the reaction was carried out at this temperature for 40 minutes. The colloid mill was turned on to accelerate the swelling process and make the modifier polypropylene more completely homogenized. After 2.2 hours, the colloid mill was stopped, and the mixture was stirred at a constant speed for 2 hours. The light stabilizer obtained in Example 2, the antioxidant obtained in Example 5, and carbon black were added, and the reaction was continued for 85 minutes to obtain an elastomer-modified asphalt rubber.
[0093] The cycloalkyl petroleum asphalt was heated to 155°C, and then maleic acid, SBS, polypropylene and polyisobutylene were added, stirred evenly, and the temperature was continued to rise to 175°C. The mixture was reacted at this temperature for 40 minutes, and the colloid mill was turned on to accelerate the swelling process and make the modifier polypropylene more completely homogenized. After 1.7 hours, the colloid mill was stopped, polyolefin acetate, the light stabilizer obtained in Example 2 and the antioxidant obtained in Example 5 were added, stirred at a uniform speed for 2 hours, and carbon black was added. The mixture was stirred and reacted for 85 minutes to prepare the high temperature resistant hot air assisted self-adhesive polymer modified asphalt rubber used in the present invention;
[0094] The isolation membrane is laid on one side of the self-adhesive polymer modified asphalt rubber layer, a polyester base layer is adhered to the other side of the self-adhesive polymer modified asphalt rubber layer, a glass fiber base layer is adhered to the surface of the polyester base layer, and a mineral granular layer is adhered to the surface of the glass fiber base layer to obtain an aging-resistant waterproof membrane.
[0095] Example 9
[0096] An aging-resistant waterproof roll material is a multi-layer structure, including a self-adhesive polymer modified asphalt rubber layer, a polyester base layer, a glass fiber base layer and a mineral granular layer. An isolation membrane is provided between the surface of one side of the self-adhesive polymer modified asphalt rubber layer and the roof, and the polyester base layer is adhered to the other side of the self-adhesive polymer modified asphalt rubber layer; the self-adhesive polymer modified asphalt rubber layer is adhered to one side of the polyester base layer, and the glass fiber base layer is adhered to the other side; the polyester base layer is adhered to one side of the glass fiber base layer, and the mineral granular layer is adhered to the other side; adjacent layers are adhered by elastomer modified asphalt rubber. The mineral granular layer is a ceramic magma material, the glass fiber base layer is a glass fiber non-woven fabric, the polyester base layer is a multifunctional polyester spunbond non-woven fabric, and the isolation membrane is a PE isolation membrane.
[0097] The elastomer modified asphalt rubber comprises the following raw materials in parts by weight: 40 parts of cycloalkyl petroleum asphalt, 20 parts of natural rock asphalt, 20 parts of cycloalkyl oil, 10 parts of SBS, 15 parts of polypropylene, 4 parts of acrylic rubber, 1 part of light stabilizer, 1 part of antioxidant and 20 parts of carbon black.
[0098] The self-adhesive polymer modified asphalt rubber comprises the following raw materials in parts by weight: 45 parts of cycloalkyl petroleum asphalt, 20 parts of maleic acid, 12 parts of SBS, 13 parts of polypropylene, 6 parts of polyisobutylene, 4 parts of polyolefin acetate, 1.5 parts of light stabilizer, 1.5 parts of antioxidant and 25 parts of carbon black.
[0099] The weight and size of each layer of the aging-resistant waterproof roll material are as follows: the total thickness of the roll material is 6 mm, the lap width is 100 mm, the length of the roll material is 1000 mm, the thickness of the self-adhesive polymer modified asphalt rubber is 2 mm, the thickness of the polyester base layer is 1.0 mm, and the gram weight is 220 g / m 2 The thickness of the glass fiber base layer is 0.5mm and the weight is 100g / m 2 The thickness between the polyester base layer and the glass fiber base layer is 1.5mm, and the thickness of the mineral aggregate is 1.2mm.
[0100] The anti-aging waterproof coiled material is made by the following steps:
[0101] The naphthenic petroleum asphalt and natural rock asphalt were heated to 160°C, and naphthenic oil, SBS, polypropylene and acrylate rubber were added in sequence, stirred evenly, and the temperature was continued to rise to 190°C, and the reaction was carried out at this temperature for 45 minutes. The colloid mill was turned on to accelerate the swelling process and make the modifier polypropylene more completely homogenized. After 2.5 hours, the colloid mill was stopped, and the mixture was stirred at a constant speed for 2 hours. The light stabilizer obtained in Example 3, the antioxidant obtained in Example 6, and carbon black were added, and the reaction was continued for 90 minutes to obtain an elastomer-modified asphalt rubber.
[0102] The cycloalkyl petroleum asphalt was heated to 160°C, and then maleic acid, SBS, polypropylene and polyisobutylene were added, stirred evenly, and the temperature was continued to rise to 180°C, and the reaction was carried out at this temperature for 45 minutes. The colloid mill was turned on to accelerate the swelling process and make the modifier polypropylene more completely homogenized. After 2 hours, the colloid mill was stopped, polyolefin acetate, the light stabilizer obtained in Example 3 and the antioxidant obtained in Example 6 were added, stirred at a uniform speed for 2 hours, and carbon black was added. The reaction was continued with stirring for 90 minutes to prepare the high temperature resistant hot air assisted self-adhesive polymer modified asphalt rubber used in the present invention;
[0103] The isolation membrane is laid on one side of the self-adhesive polymer modified asphalt rubber layer, a polyester base layer is adhered to the other side of the self-adhesive polymer modified asphalt rubber layer, a glass fiber base layer is adhered to the surface of the polyester base layer, and a mineral granular layer is adhered to the surface of the glass fiber base layer to obtain an aging-resistant waterproof membrane.
[0104] Comparative Example 1
[0105] This comparative example is a commercially available waterproof membrane.
[0106] Comparative Example 2
[0107] Compared with Example 9, the light stabilizer was replaced with (2,2,6,6-tetramethyl-4-piperidinyl) sebacate, and the other steps were exactly the same as in Example 9 to obtain an aging-resistant waterproof membrane.
[0108] Comparative Example 3
[0109] Compared with Example 9, the antioxidant was replaced with kaolin, and the rest was exactly the same as Example 9 to obtain an aging-resistant waterproof membrane.
[0110] The aging-resistant waterproof membrane prepared by the present invention is further tested for its effect, and the test results are as follows.
[0111] In order to test the aging-resistant waterproof membrane prepared by the present invention, the test was carried out according to "GB 18242-2008 Elastomer-modified asphalt waterproof membrane" and "GB 328-2007 Test method for building waterproof membrane", and the results are shown in Table 1:
[0112] Table 1:
[0113]
[0114] According to the data in Table 1, compared with Example 1, it can be seen that the mechanical properties, aging resistance, waterproof performance and heat resistance of the aging-resistant waterproof roll prepared by the present invention are higher than those of commercially available waterproof rolls; compared with Comparative Example 2, Example 9 shows that compared with (2,2,6,6-tetramethyl-4-piperidinyl) sebacate without the introduction of fluorine element, the use of a synthetic light stabilizer enhances the aging resistance of the material, and the hydrophobicity and lipophilicity of the polyfluoroalkyl group enhance the waterproof performance of the waterproof roll; compared with Comparative Example 3, Example 9 shows that compared with kaolin, kaolin modified with a silane coupling agent is used as an antioxidant, and the kaolin with a toughening effect is easier to disperse and be compatible in the modified asphalt through chemical bonding, and the mechanical properties and aging resistance of the material are improved. At the same time, the introduction of trifluoroethoxy enhances the waterproof performance of the waterproof roll, and the good thermal stability of the silane ether group improves the thermal stability of the material.
[0115] The above contents are merely examples and explanations of the concept of the present invention. The technicians in this technical field may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the concept of the invention or exceed the scope defined by the claims, they should all fall within the protection scope of the present invention.
Claims
1. An aging-resistant waterproof coiled material, characterized in that: The multi-layer structure comprises a self-adhesive polymer modified asphalt rubber layer, a polyester base layer, a glass fiber base layer and a mineral granular material layer; an isolation film is arranged between the surface of one side of the self-adhesive polymer modified asphalt rubber layer and the roof, and the polyester base layer is adhered to the surface of the other side of the self-adhesive polymer modified asphalt rubber layer; the self-adhesive polymer modified asphalt rubber layer is adhered to the surface of one side of the polyester base layer, and the glass fiber base layer is adhered to the surface of the other side; the polyester base layer is adhered to the surface of one side of the glass fiber base layer, and the mineral granular material layer is adhered to the surface of the other side; adjacent layers are adhered to each other by means of an elastomer modified asphalt rubber; The mineral granular material layer is ceramic magma material, the glass fiber base layer is glass fiber non-woven fabric, the polyester base layer is multifunctional polyester spunbond non-woven fabric, and the isolation membrane is a PE isolation membrane.
2. The aging-resistant waterproof coiled material according to claim 1, characterized in that: The elastomer modified asphalt rubber comprises the following raw materials in parts by weight: 20-40 parts of cycloalkyl petroleum asphalt, 10-20 parts of natural rock asphalt, 10-20 parts of cycloalkyl oil, 7-10 parts of SBS, 10-15 parts of polypropylene, 2-4 parts of acrylic rubber, 0.5-1 parts of light stabilizer, 0.5-1 parts of antioxidant and 10-20 parts of carbon black; the self-adhesive polymer modified asphalt rubber comprises the following raw materials in parts by weight: 35-45 parts of cycloalkyl petroleum asphalt, 15-20 parts of maleic acid, 8-12 parts of SBS, 8-13 parts of polypropylene, 4-6 parts of polyisobutylene, 3-4 parts of polyolefin acetate, 0.5-1.5 parts of light stabilizer, 0.5-1.5 parts of antioxidant and 10-25 parts of carbon black.
3. The aging-resistant waterproof coiled material according to claim 1, characterized in that: The elastomer-modified asphalt rubber is prepared by the following steps: Heat cycloalkane petroleum asphalt and natural rock asphalt to 150-160℃, add cycloalkane oil, SBS, polypropylene and acrylic rubber in turn, stir evenly, continue to heat to 180-190℃, react at this temperature for 35-45min, start the colloid mill to accelerate the swelling process and make the modifier polypropylene more homogenized, stop the colloid mill after 2-2.5h, stir at a constant speed for 2h, add light stabilizer, antioxidant, carbon black, continue to react for 80-90min, and obtain the elastomer modified asphalt rubber.
4. The aging-resistant waterproof coiled material according to claim 1, characterized in that: The self-adhesive polymer modified asphalt rubber is prepared by the following steps: Heat cycloalkyl petroleum asphalt to 150-160°C, then add maleic acid, SBS, polypropylene and polyisobutylene, stir evenly, continue to heat to 170-180°C, react at this temperature for 35-45 minutes, start the colloid mill to accelerate the swelling process, and make the modifier polypropylene more completely homogenized, stop the colloid mill after 1.5-2 hours, add polyolefin acetate, light stabilizer and antioxidant, stir at a uniform speed for 2 hours, add carbon black, continue stirring and reacting for 80-90 minutes, and prepare the high temperature resistant hot air assisted self-adhesive polymer modified asphalt rubber used in the present invention.
5. The aging-resistant waterproof coiled material according to claim 1, characterized in that: The light stabilizer is prepared by the following steps: Step A1: 2,2,6,6-tetramethylpiperidinol was added to methanol, and then a 2 mol / L sodium bicarbonate solution was added, and di-tert-butyl dicarbonate was added under stirring, and the mixture was stirred at 60° C. for 4 h, cooled, filtered, washed with deionized water, and vacuum dried at 65° C. for 8 h to obtain intermediate 1; Step A2: Dissolve the intermediate 1 in methanol, add dimethyl sulfoxide, stir to dissolve, add perfluorosebacic acid with stirring, then heat under reflux at 70°C for 2h, cool, filter, extract with ether, and vacuum dry at 75°C for 6h to obtain the intermediate 2; Step A3: Add intermediate 2 to trifluoroacetic acid, stir, and react at room temperature for 1-2 hours, then add it to deionized water, stir, extract with ethyl acetate, and rotary evaporate to obtain a light stabilizer.
6. An aging-resistant waterproof coiled material according to claim 5, wherein in step A1, the amount ratio of 2,2,6,6-tetramethylpiperidinol, methanol, 2 mol / L sodium bicarbonate solution and di-tert-butyl dicarbonate is 0.1-0.2 mol:150 mL:200 mL:0.05 mol, in step A2, the amount ratio of intermediate 1, methanol, dimethyl sulfoxide and perfluorosebacic acid is 0.2 mol:150 mL:2-3 mL:0.1 mol, and in step A3, the amount ratio of intermediate 2 and trifluoroacetic acid is 0.1 mol:0.3-0.4 mol.
7. The aging-resistant waterproof coiled material according to claim 1, characterized in that: The antioxidant is prepared by the following steps: Step B1: 3-aminopropyltrichlorosilane was added to n-hexane under the protection of nitrogen, and the mixture was dissolved by stirring to obtain a mixed solution. Then, the mixed solution was dripped into trifluoroethanol under the protection of nitrogen flow, and the mixture was stirred at 50° C. for 3 h to obtain intermediate 3; Step B2: Dissolve γ-methacryloxypropyltrimethoxysilane in methanol, add sodium carbonate, add tert-butyl peroxide with stirring, react at room temperature with stirring for 2 hours, and extract with ether to obtain intermediate 4; Step B3: Dissolve intermediate 4 in methanol, add sodium hydroxide, add intermediate 3 under stirring, react at room temperature with stirring for 6 hours, and extract with ether to obtain intermediate 5; Step B4: dissolving tert-butyldimethylsilyl chloride in DMF, adding intermediate 5 under stirring, and reacting under stirring at room temperature for 1.5 h to obtain a silane coupling agent; Step B5: Mix the silane coupling agent and a 95% ethanol solution by volume in a beaker and ultrasonically disperse for 30 minutes to obtain a silane coupling agent hydrolyzate; pour kaolin and deionized water into a three-necked flask to prepare a kaolin slurry, add the silane coupling agent hydrolyzate while stirring, control the temperature to 80°C and stir at a speed of 500 r / min for 4 hours, and filter under reduced pressure after cooling. Wash the filter cake with anhydrous ethanol for multiple times to remove unreacted silane coupling agent, put the filter cake into a vacuum drying oven at 80°C and dry it for 2 hours. After cooling, grind it and pass it through a 300-mesh sieve to obtain an antioxidant.
8. The aging-resistant waterproofing membrane according to claim 6, wherein in step B1, the amount ratio of 3-aminopropyltrichlorosilane, n-hexane and trifluoroethanol is 0.1 mol: 200 mL: 0.3-0.4 mol, the amount ratio of γ-methacryloxypropyltrimethoxysilane, methanol, sodium carbonate and tert-butyl peroxide in step B2 is 0.1 mol: 150 mL: 0.02 g-0.04 g: 0.2-0.3 mol, and the amount ratio of γ-methacryloxypropyltrimethoxysilane, methanol, sodium carbonate and tert-butyl peroxide in step B3 is 0.1 mol: 150 mL: 0.02 g-0.04 g: 0.2-0.3 mol. In step B3, the amount ratio of intermediate 4, sodium hydroxide and intermediate 3 is 0.1 mol: 0.02-0.03 g: 0.1 mol, the amount ratio of tert-butyldimethylchlorosilane, DMF and intermediate 5 in step B4 is 0.1 mol: 150 mL: 0.1 mol, and the amount ratio of silane coupling agent, 95% ethanol solution by volume, kaolin and deionized water in step B5 is 0.5 g: 50 mL: 20 g: 400 mL.
Citation Information
Patent Citations
Self-adhesive waterproof membrane
CN107642172B